Wheat lignans: Promising cancer preventive agents - Wang, Weiqun; Ayella, Allan; Jiang, Yu; Ouyang, Ping; Qu, Hongyan (John Wiley & Sons, Inc., 2008)
Consumption of dietary fibers, particularly fibers from wheat bran, has been associated with a reduced risk of colorectal cancer. However, the experimental evidence by using different fiber sources on colon cancer prevention is controversial. A previous study by applying same amount of wheat fibers but from various wheat cultivars in APCMin mouse model demonstrated a significant difference in anti-tumor activity. In addition to fibers, wheat bran consists of many antioxidant phytochemicals such as lignans that may account for, at least in part, the discrepancy. Lignans are a group of the phytochemicals that compose of phenylpropane dimer linked by beta-beta bonds with a 1,4-diarylbutane structure. Lignans are usually rich in flaxseed but also present in grain brans. In wheat bran, the prominent lignan is secoisolariciresinol diglycoside (SDG) that, if consumed, is converted by intestinal microflora to lignan metabolites. Although epidemiological studies have observed a conflict ing correlation between the circulating levels of lignan metabolites and colorectal cancer risk, most of preclinical and animal model studies have consistently shown a cancer preventive role of dietary lignans. Our studies indicated that dietary SDG at 0.01% significantly suppressed azoxymethane-induced formation of aberrant crypt foci in F344 rats. Furthermore, we recently found that the contents of lignans in wheat bran from various cultivars were correlated with anti-tumorigenesis in spontaneous APCMin mouse model. These observations, coupled with the established mechanisms by which lignans and/or lignan metabolites may exert anticancer activities, indicate lignans may attribute to the observed colon cancer prevention by wheat bran or whole grain products.
Keywords: Wheat lignans; Cancer prevention; Secoisolariciresinol diglycoside; Aberrant crypt foci; Whole grain